The predictive function of Swedish word accents - Roll, Mikael (Frontiers in Psychology, 2022)
Swedish lexical word accents have been repeatedly said to have a low functional load. Even so, the language has kept these tones ever since they emerged probably over a thousand years ago. This article proposes that the primary function of word accents is for listeners to be able to predict upcoming morphological structure rather than being lexically distinctive. Psycho- and neurophysiological evidence for the predictive function of word accents is discussed. A new analysis displays that word accents have a facilitative role in word processing. Specifically, a correlation is revealed between how much incorrect word accents hinder listeners’ processing and how much they reduce response time when correct. Finally, a dual-route model of the predictive use of word accents with distinct neural substrates is put forth.